A Study on Sector Wise Comparative Analysis of NPAs of Public Sector and Private Sector Bank in India - Ms. Swati Prajapat, Dr. Nupur Ojha (International Journal of Advanced Science and Technology, 2020)
Various studies have realized that the public sector banks lacks as compared to private sector banks fromthe view point of NPA position. So this study carry out the sector wise comparative analysis of two banksviz., one from the public sector banks i.e. State Bank of India and Punjab National Bank and the other fromthe private sector banks i.e. ICICI bank and AXIS Bank. This study aim to reveal the actual sector wiseNPA position of both the banks and to do their comparative analysis to identify which sector is the highestNPA making in these banks. Also this study compares the sector wise target achievement with reference topriority sector lending and their sector wise profitability. So that it will be identified that which sector ofeconomy is non-performing for these banks.